The logic of the history of ideas - Bevir, Mark (Cambridge University Press, 1999)
Mark Bevir's book explores the forms of reasoning appropriate to the history of ideas, enhancing our understanding by grappling with central questions such as: What is a meaning? What constitutes objective knowledge of the past? What are beliefs and traditions? How can we explain why people held the beliefs they did? The book ranges widely over issues and theorists associated with post-analytic philosophy, post-modernism, hermeneutics, literary theory, political thought and social theory.